Assessment of occupational burnout among private dental practioners in Bengaluru city -a cross sectional study - Reddy, MayurNath; HL, Shwetha; Mishra, Mayur (International Journal of Dental Research, 2017)
Introduction: Dentistry is highly rewarding profession, but it’s very demanding job with high degree of concentration and precision in work. Dentists seem to be prone to professional burnout, anxiety disorders and clinical depression because of the variety of sources of stress encountered throughout the professional career.Objectives: To assess the burnout level and physical exhaustion among private dental practitioners.Materials and methods: A cross sectional study was carried out on private dental practitioners in Bengaluru city. A questionnaire containing 22 items Maslach Burnout Inventory and demographic detail, was administered. The response rates were obtained using a likert scale ranging from 0-6. Analysis for p value, cronbach’s α for each questions (>0.700 = high consistency), frequency and comparison of variables, were done.Results: The study found high level of burnout in 11.3% of participants. It also showed age group of <=25 and 25-35, females were highly influenced. More amount of burnout level found in general practitioners than specialists. Study also indicates that backache 48% and headache 44.7%were main reasons for physical exhaustion followed byneck-ache 34%and hand and wrist disorders 23.7%.Conclusion: As health care provider the dentists are subjected to interpersonal stress due to the demanding nature of the occupation and close proximity to the patient.Moderate to high level of burnout were detected in the study sample, it’s recommended that attention for burnout risk should be given priority by dental professionals.